ANALISIS PENGARUH INFORMASI KEUANGAN DAN NON KEUANGAN TERHADAP INITIAL RETURN DAN RETURN 10 HARI SETELAH INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA TAHUN 2012-2016 - ABDULRAHMAN, DIMAS; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2017)
This research is aimed to examine the inflence of (1) financial information and non financial information to initial return and (2)financial information and non financial information to 10 days return after IPO. Multiple regression method used to analyse the data. The result of analysis for the influence of financial information and non financial information to initial return shows that only underwriter reputation and company size significantly influences. Whereas current ratio, debt equity ratio, return on equity, earning per share, auditor reputation, and percentage of shared offered to the public do not significantly influence to initial return. The result of analysis for the influence of financial information and non financial information to 10 days return after IPO shows that all of the variables which are current ratio, debt equity ratio, return on equity, earning per share, underwriter reputation, auditor reputation, company size, and percentage of shared offered to the public do not significantly influence to10 days return after IPO.